Preschoolers Reduce Inequality While Favoring Individuals With More. Issue 3 (6th December 2013) - Li, Vivian; Spitzer, Brian; Olson, Kristina R.
Abstract : Inequalities are everywhere, yet little is known about how children respond to people affected by inequalities. This article explores two responses—minimizing inequalities and favoring those who are advantaged by them. In Studies 1a ( N  = 37) and 1b ( N  = 38), 4‐ and 5‐year‐olds allocated a resource to a disadvantaged recipient, but judged advantaged recipients more positively. In Studies ( N  = 38) and ( N  = 74), a delay occurred between seeing the inequality and allocating resources, or stating a preference, during which time participants forgot who was initially more advantaged. Children then favored advantaged recipients on the preference and resource allocation measures, suggesting an implicit "affective tagging" mechanism drives the tendency to favor the advantaged. In contrast, reducing inequalities through resource allocation appears to require explicit reasoning.